Analysing the Correlation of Bank Sampah and Rural Environmental Government Concept - Adibah Dhivani Gusmi; Rahmawati Husein (Jurnal Ilmu Lingkungan, 2023)
This study aims to analyze the concept of Bank sampah as the rural environmental government in Indonesia. The initial reason for researching these issues is supported by the importance of collaborative governance in rural governmental organization. At this case, villagers and bank sampah is the key for this issue. The work of villagers who run the technical bank sampah necessities are need to be strengthen by local government and other stakehilders such as private, or any other non-governmental organization. Behavioural change that supposed to be existing at the beginning of bank sampah initials is broken down into several stages that also needed to be implemented by all the stakeholders. Using qualitative methods with a multiple case study approach, the researchers focused on Bank Sampah itself, community participation, and also rural environmental government in Indonesia in order to support the execution of the 3 R (reduce, reuse, and recycle) and promote behavioral change in society, Bank Sampah was founded. The government needs to establish strict regulations for stakeholder collaboration. Rural environmental governance and sustainable development are inextricably linked to village involvement as well as the rule of virtue and the rule of the people, not just from government's point of view. Also, with strong local government and environmental protection, there is hope that Indonesia's ecological civilisation will advance, particularly with the implementation of Bank Sampah.